Estimating ocean wave directional spreading from an Eulerian surface elevation time history - Adcock, T; Taylor, P (2009)
The directional spreading of sea states is an important design parameter in offshore engineering. Wave directionality affects the resulting wave kinematics, which affects the forces exerted on offshore structures. In this paper, we develop a method for estimating the amount of spreading, when the only information available is the time history of free surface elevation at a single point in space. We do this by predicting the second-order bound waves that occur at the difference in frequency of two freely propagating waves. The magnitude of these second-order bound waves is a function of the angle between the interacting waves. Thus, it is possible to infer some information about spreading from a single-point time history. We demonstrate that this approach works for wave groups in a fully nonlinear numerical wave tank. We create a synthetic random sea state and introduce noise into the analysis and thus show that our approach is robust and insensitive to noise, even with a signalto-noise ratio of unity in the difference waves. This approach is also applied to random waves in a physical wave tank where spreading was directly measured and also to a storm recorded in the North Sea. In all cases, we find our estimate of spreading is in good agreement with other measurements. © 2009 The Royal Society.